Synthesis and Characterization of some Pyrazoline derivatives from Chalcones containing azo and ether groups - Ahmed A. ALKazmi; Farouq Emam Hawais; Yuosra K. Alasadi (Tikrit Journal of Pure Science, 2023)
A number of 3-(substituted)-5-(2((4-chlorobenzyl)oxy)-5-(m-tolyldizenyl) pheny l) pyrazoline (3a-j) have been synthesized by benzyloxation of hydroxyl group to give the substrate 2-((4-chlorobenzyl)oxy)-5-(m-tolyldizenyl) benzaldehyde (1). The compound (1) has been treated with different substituted acetophenone to give a new series of chalcone derivatives 1-(substituted)-3-(2-((4-chlorobenzyl)oxy)-5-(m-tolyldiazenyl) phenyl) prop-2-en-1-one (2a-j). The chalcone derivatives have been treated with hydrazine hydrate according to Michael addition reaction to afford a series of new pyrazoline derivatives. The characterization of the newly synthesized compounds elucidated by FT-IR, 1H-NMR, 13C-NMR, 13C-DEPT and elemental analyses